Circular RNA circ‐Foxo3 inhibits esophageal squamous cell cancer progression via the miR‐23a/PTEN axis - Xing, Yao; Zha, Wen‐Juan; Li, Xiao‐Min; Li, Hao; Gao, Fei; Ye, Ting; Du, Wang‐Qi; Liu, Yang‐Chen (Journal of cellular biochemistry, 2020)
Circ‐Foxo3 is a circRNA encoded by the human FOXO3 gene and works as a sponge for potential microRNAs (miRNAs) to regulate cancer progression. However, the role of circ‐Foxo3 in esophageal squamous cell cancer (ESCC) is not clear. In this study, circ‐Foxo3 was lowly expressed in cell lines and ESCC tissues. Meanwhile, overexpression of circ‐Foxo3 inhibited cell growth, migration, and invasion, whether in vivo or in vitro. Mechanically, we found a potential miRNA target, miR‐23a, which negatively correlated with circ‐Foxo3 in ESCC. Then, a luciferase assay confirmed the relationship between the circ‐Foxo3 and miRNA. Moreover, circ‐Foxo3 upregulation of PTEN occurred through “sponging” miR‐23a. Taken together, these results indicated that the circ‐Foxo3/miR‐23a/PTEN pathway was critical for inhibiting the ESCC progression. This may provide a promising target for treat ESCC. The circ‐Foxo3/miR‐23a/PTEN pathway is possibly a critical factor in inhibiting esophageal squamous cell cancer (ESCC) progression. This may provide a promising target for treating ESCC.